The Effect of Drug Hazard Counselling in Improving Public Knowledge Level of Hazardous Drugs - Reny Jabar; Sri Nurhayati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
The drugs abuse (narcotics, psychotropic and addictive substances) from year to year has been increasing. Drug abuse is a threat and complex problem that can destroy the society. This research is expected to describe the effectiveness of public counselling conducted by BNN West Bandung Regency on the prevention of drug abuse on the knowledge of society. This research was conducted in 2021 in Cigugur Girang Village of West Bandung Regency. This research used quantitative approach with pre-experimental one group pretest-posttest design. The results of the analysis with the paired sample t-test showed that there is a difference between the final understanding and the initial understanding of the community who received counseling on drug hazards, implying that counseling activities are extremely effective in improving public knowledge level of hazardous drugs.